Lumières de Lyon - Blanc, Théo 1891-1985; Demilly, Antoine 1892-1964 (1950)
"Publication with 18 original silver prints. All but one taken at night of buildings and statues of Lyon by these famous French photographers." (Beschreibung des Antiquariats)
Spiralbindung. - 18 Silbergelatine-Drucke
Keywords: Demilly, Antoine -- 1892-1964; Blanc, Théo -- 1891-1985; Fotografie; Nachtfotografie; Lyon; Bildband